Development and Validation of a Cross-Cultural Heart Failure-Specific Quality of Life Questionnaire - Siti Raudzah, Ghazali; Nor Firdous, Mohamed; Nor A., Yaacob; Aizai Azan, Abdul Rahim; Oteh, Maskon (Sultan Qaboos University, 2018)
Objectives: Heart failure (HF) is a common clinical syndrome with an enormous impact on prognosis and lifestyle. Accordingly, rehabilitation measures need to be patient-specific and consider various sociocultural factors so as to improve the patient’s quality of life (QOL). This study aimed to develop and validate a HF-specific QOL (HFQOL) questionnaire within a multicultural setting. Methods: This study took place at the National Heart Institute and Universiti Kebangsaan Malaysia Medical Centre, Kuala Lumpur, Malaysia, between March 2013 and March 2014. A self-administered 75-item HFQOL questionnaire was designed and administrated to 164 multi-ethnic Malaysian HF patients. Exploratory factor analysis was performed to assess the instrument’s construct validity. Cronbach’s alpha coefficients were used to determine internal consistency. Results: A total of 33 out of 75 items were retained in the final tool. The HFQOL questionnaire had three common factors—psychological, physical-social and spiritual wellbeing—resulting in a cumulative percentage of total variance of 44.3%. The factor loading ranges were 0.450–0.718 for psychological wellbeing (12 items), 0.394–0.740 for physical-social wellbeing (14 items) and 0.449–0.727 for spiritual wellbeing (seven items). The overall Cronbach’s alpha coefficient of the questionnaire was 0.82, with coefficients of 0.86, 0.88 and 0.79 for the psychological, physical-social and spiritual wellbeing subdomains, respectively. Conclusion: The HFQOL questionnaire was found to be a valid and reliable measure of QOL among Malaysian HF patients from various ethnic groups. Such tools may facilitate cardiac care management planning among multi-ethnic patients with HF.